When Mindfulness Interacts With Neuroticism to Enhance Transformational Leadership: The Role of Psychological Need Satisfaction - Decuypere, Anouk; Audenaert, Mieke; Decramer, Adelien (Frontiers in Psychology, 2018)
Transformational leadership is a popular and well-researched leadership style. Although much is understood about its positive consequences, less research has focused on antecedents of transformational leadership. In this research we draw upon self-determination theory and incorporate a self-regulatory approach to investigate if and how leader mindfulness influences transformational leadership. The analyses show that autonomy, competence and relatedness need satisfaction mediate between mindfulness and transformational leadership, indicating that mindfulness is associated with psychological need satisfaction. Furthermore, the data show that neuroticism moderates the relationship between mindfulness and relatedness need satisfaction. Generally speaking, the association between mindfulness and relatedness need satisfaction is positive. When neuroticism is also high, mindfulness has the largest impact. Or conversely, when emotional stability is high, mindfulness has the smallest association with relatedness need satisfaction. This is in line with evidence suggesting that mindfulness may primarily exert its influence through emotional self-regulation. Furthermore, the moderated mediation model for relatedness satisfaction is significant, indicating that neuroticism is a boundary condition for the indirect effect of mindfulness on transformational leadership through relatedness need satisfaction.